Legendary sagas as historical sources - Hans Jacob Orning (Tabularia)
This article advocates using legendary sagas as historical sources, since these texts in spite of their non-realistic content, can tell historians a lot about the context in which the stories were written, and hence about the conditions that the people listening to them lived under. Using legendary sagas this way presupposes that they are read in their manuscript context, in line with the methodology of New Philology. However, this approach also brings along several challenges, some of which are addressed in this article. One practical challenge is to situating the manuscript historically, but in this field paleographists have done extensive work. Second, sagas are normally contained in manuscripts containing numerous sagas. This article argues that sagas should not be isolated from their manuscript context, and that manuscripts should be interpreted as totalities, not as random collections of sagas. Finally, legendary sagas deal with adventurous, allegedly “unhistorical”, events. Yet, using the handling of these themes as keys to mentalities can open up new venues for historians, provided that they abandon a narrow definition of what should be considered “historical”.